2022
DOI: 10.47836/pjst.30.2.19
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Blood-Based Multi-Omics Biomarkers for Alzheimer’s Disease Using Firth’s Logistic Regression

Abstract: Alzheimer’s disease (AD) is a progressive and relentless debilitating neurodegenerative disease. A post-mortem microscopic neuropathological examination of the brain revealed the existence of extracellular β-amyloid plaques and intracellular neurofibrillary tangles. An accurate early diagnosis of AD is difficult because various disorders share the initial symptoms of the disease. Based on system biology, the multi-omics approach captures and integrates information from genomics, transcriptomics, proteomics, cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…However, there were common themes between some studies which caused the reviewers to rate 6 of the 22 papers with a medium or high risk of bias. The only study with a high risk of bias was Abdullah et al [35], which reported a prediction accuracy of 100% with a dataset of only 47 individuals and no reported means of data validation. The other 5 medium risk of bias studies were the papers of Yu et al, Darst et al, Binder et al, Khullar and Wang, and Francois et al[36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there were common themes between some studies which caused the reviewers to rate 6 of the 22 papers with a medium or high risk of bias. The only study with a high risk of bias was Abdullah et al [35], which reported a prediction accuracy of 100% with a dataset of only 47 individuals and no reported means of data validation. The other 5 medium risk of bias studies were the papers of Yu et al, Darst et al, Binder et al, Khullar and Wang, and Francois et al[36].…”
Section: Resultsmentioning
confidence: 99%
“…The only study with a high risk of bias was Abdullah et al [35], which reported a prediction accuracy of 100% with a dataset of only 47 individuals and no reported means of data validation. The other 5 medium risk of bias studies were the papers of…”
Section: Risk Of Bias In Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent finding of using hybrid anova and lasso methods for feature selection of microarray data and testing on spark environment denoted that RF perform best with 100% in two dataset and 96% in one dataset in a less time consumed [10]. Other applications of machine learning approach particularly on predictive models could be found in various field of studies including intervention and prevention of diabetic retinopathy [11], diagnosis of Alzheimer's disease [12], prediction of dengue outbreaks [13] and heart failure [14], prediction and classification on future PM10 concentrations [15], forecasting reservoir water level [16], forecasting daily sales data [17] and rainfall prediction in flood prone areas [18] and brain MRI image classification for Alzheimer's disease [19].…”
Section: Introductionmentioning
confidence: 99%

Classification of Breast Cancer Subtypes using Microarray RNA Expression Data

Muhammad Shazwan Suhiman,
Sayang Mohd Deni,
Ahmad Zia Ul-Saufie Mohamad Japeri
et al. 2024
ARASET